Solid electrolyte material and preparation method thereof

By mixing and lithium salt of biodegradable materials, polyethylene glycol, and ethylene-acrylic-acrylic methacopenic polymer and lithium salt, prepare solid electrolyte materials with high mechanical strength and high ion conductivity, solving the existing materials in mechanical machinery Insufficient strength and ion conductivity have achieved the ability of biodegradable performance.

CN119381576APending Publication Date: 2025-01-28HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411549682.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The solid electrolyte materials in existing all-solid-state lithium batteries have shortcomings in terms of mechanical strength and ionic conductivity, and traditional materials are difficult to achieve biodegradable properties.

Method used

By mixing and cutting biodegradable materials, polyethylene glycol, and ethylene-acrylic methacopicate cluster to form mixed materials, and mix with lithium salts to prepare solid electrolytes with high mechanical strength and high ion conductivity Material.

Benefits of technology

The mechanical performance improvement of materials, increased ionic conductivity, and biodegradable performance are suitable for all solid -state lithium batteries, which improves the safety performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381576A_ABST
    Figure CN119381576A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte material and a preparation method thereof, and relates to the technical field of lithium ion batteries. The preparation method of the solid electrolyte material comprises the following steps: S1, mixing and shearing a biodegradable material, polyethylene glycol and an ethylene-methyl acrylate copolymer to obtain a mixed material; and S2, uniformly mixing the first part of mixed material with a lithium salt, adding the second part of mixed material, mixing, and shearing to obtain the solid electrolyte material. The solid electrolyte material prepared by the invention has the advantages of biodegradability, high ionic conductivity and high mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid electrolyte material and a preparation method and application thereof. Background Art

[0002] All-solid-state lithium batteries use polymer-based solid electrolytes to replace the electrolytes used in traditional lithium-ion batteries, greatly improving the safety and long-cycle performance of lithium batteries. Biodegradable materials can be biodegraded in nature. Among them, polylactic acid (PLA) is polymerized from lactic acid. As a new type of green and environmentally friendly biodegradable material, the production process of polylactic acid does not cause pollution, the source of raw materials is sufficient, and the product can be degraded by organisms, thus forming a cycle in nature. As a green polymer material, it is becoming a research hotspot. Modifying biodegradable materials and expanding their performance to synthesize green biodegradable solid electrolyte materials to meet the demand for solid electrolytes in the field of all-solid-state batteries is of great significance to the development of solid-state batteries. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a solid electrolyte material and a preparation method and application thereof.

[0004] A method for preparing a solid electrolyte material proposed by the present invention comprises the following steps:

[0005] S1. mixing and shearing the biodegradable material, polyethylene glycol and ethylene-methyl acrylate copolymer to obtain a mixed material;

[0006] S2. After the first part of the mixed material and the lithium salt are evenly mixed, the second part of the mixed material is added, and the mixed materials are mixed and sheared to obtain a solid electrolyte material.

[0007] The invention enhances the material strength and ion conductivity by modifying the polyethylene glycol-based polymer electrolyte, and further makes the material biodegradable by introducing biodegradable materials for melt blending, thereby becoming a new green solid electrolyte.

[0008] Preferably, in S1, the biodegradable material is selected from one or more of polylactic acid, polycaprolactone, polylactic acid-polyethylene glycol copolymer, and polydioxanone.

[0009] Preferably, in said S1, the molecular weight of polyethylene glycol is 600-10000.

[0010] Preferably, in S1, the ethylene-methyl acrylate copolymer is ethylene-methyl acrylate grafted glycidyl methacrylate EMA-g-GMA, wherein the GMA monomer content is 5-12wt%, the methyl acrylate content is 22-26wt%, and the melt index is 3-8g / 10min (190°C / 2.16kg).

[0011] Preferably, in said S1, the mass ratio of the biodegradable material, polyethylene glycol and ethylene-methyl acrylate copolymer is (30-40):(5-15):(5-15).

[0012] Biodegradable materials can be biodegraded in nature. At present, with the growing development of the new energy industry, the recycling of waste batteries is facing tremendous pressure. The present invention adopts polylactic acid as one of the synthetic materials of the solid electrolyte. Compared with ordinary organic polymers, it can reduce the harm to the environment and also reduce the cost of treating waste batteries. Polyethylene glycol has good lithium salt solubility and can be complexed with a variety of lithium salts. It is widely used in the synthesis of various solid electrolytes. The present invention introduces polyethylene glycol to increase the solubility of solid electrolyte materials to lithium salts. Due to the characteristics of the molecular chain itself, the ethylene-methyl acrylate copolymer can effectively increase the glass transition temperature of polylactic acid and polyethylene glycol and reduce the crystallinity, solving the problem of polyethylene glycol crystallization at room temperature as a solid electrolyte. In addition, the ethylene-methyl acrylate copolymer can withstand large tensile and compressive forces, effectively avoid the puncture of lithium dendrites, and improve the safety performance of solid-state batteries.

[0013] Preferably, in S1, the mixing conditions include: temperature 180-220° C., rotation speed 500-1000 r / min, and time 3-20 min.

[0014] Controlling the mixing conditions helps to fully mix the components and avoid local unevenness of the material.

[0015] Preferably, in S2, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium phosphate and lithium sulfate.

[0016] The role of lithium salt is to improve the ion conductivity of solid electrolytes, thereby improving the charge and discharge rate and power density of the entire battery.

[0017] Preferably, in S2, the mass ratio of the first part of the mixed material, the lithium salt, and the second part of the mixed material is (40-60):(0.5-5):(40-60).

[0018] Regulating the mass ratio helps control material parameters such as strength, ionic conductivity, and crystallinity, and can adapt to the performance requirements of different solid-state batteries for solid-state electrolytes.

[0019] Preferably, in S2, the sum of the amount of the first part of the mixed material and the amount of the second part of the mixed material is equal to the total amount of the mixed material.

[0020] Preferably, in said S2, the mixing conditions include: temperature 200-240°C, rotation speed 800-1200r / min, and time 5-10min.

[0021] Controlling the mixing conditions helps to fully mix the components and avoid local unevenness of the material.

[0022] The present invention also provides a solid electrolyte material prepared by the above preparation method.

[0023] Application of the solid electrolyte material proposed in the present invention or the solid electrolyte material prepared by the above preparation method in solid-state lithium batteries.

[0024] The beneficial effects of the present invention are:

[0025] The present invention mainly introduces fillers with excellent properties such as biodegradable materials, lithium salts, ethylene-methyl acrylate copolymer (EMA-g-GMA) into polyethylene glycol (PEG) to improve its ionic conductivity, mechanical properties and biodegradability. Polyethylene glycol has high crystallinity and low ionic conductivity at room temperature, but it has good lithium salt solubility and can be complexed with a variety of lithium salts. The present invention uses polyethylene glycol as a matrix and realizes material modification and performance expansion by blending and compounding with functional materials such as polylactic acid to meet the demand for solid electrolytes in the field of all-solid-state batteries.

[0026] At present, the research on PLA blended composite materials mainly focuses on the changes in the interaction forces between each phase and each component on the microstructure of the system (such as crystal region structure, two-phase interface structure, etc.), and the influence of this aspect on the macroscopic performance of the PLA blended composite system. The research on its internal connection is still relatively small. Based on this, the present invention will regulate the multi-phase and multi-component interaction forces in the blended composite system from the perspective of thermodynamics and kinetics by changing the melt blending formula and process, and explore the influence and mechanism of the change of the interaction forces between each phase and each component on the microstructure and macroscopic performance of the system, which can reveal the internal connection between the structure and performance of the PLA blended composite material, realize the efficient composite blending of PLA / PEG / EMA-g-GMA / Lithium-Salt, and form a biodegradable green solid electrolyte with high ionic conductivity and high mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The thermogravimetric curves of the materials of comparative examples 1-6 of the present invention are shown.

[0028] Figure 2 1 is the ionic conductivity curve of the materials of Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail through specific embodiments.

[0030] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0031] Ethylene methyl acrylate copolymer (EMA-g-GMA): Arkema LOTADER AX8900.

[0032] Example 1

[0033] A method for preparing a solid electrolyte material comprises the following steps:

[0034] S1, 60 parts of polylactic acid, 20 parts of polyethylene glycol (molecular weight 8000), and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer, mixed at a temperature of 200° C. and a speed of 800 r / min for 5 min, and sheared to obtain a mixed material;

[0035] S2. After 50% of the mixed material is evenly mixed with 0.5 parts of lithium bis(trifluoromethanesulfonate)imide, the remaining mixed material is added, and the material is mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes, and sheared to obtain a solid electrolyte material, which is recorded as PLA / PEG / EMA-g-GMA / 0.5L.

[0036] Example 2

[0037] A method for preparing a solid electrolyte material comprises the following steps:

[0038] S1, 60 parts of polylactic acid, 20 parts of polyethylene glycol (molecular weight 8000), and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer, mixed at a temperature of 200° C. and a speed of 800 r / min for 5 min, and sheared to obtain a mixed material;

[0039] S2. After 50% of the mixed material is evenly mixed with 1 part of lithium bis(trifluoromethanesulfonyl)imide, the remaining mixed material is added, and the material is mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes, and sheared to obtain a solid electrolyte material, which is recorded as PLA / PEG / EMA-g-GMA / 1L.

[0040] Example 3

[0041] A method for preparing a solid electrolyte material comprises the following steps:

[0042] S1, 60 parts of polylactic acid, 20 parts of polyethylene glycol (molecular weight 8000), and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer, mixed at a temperature of 200° C. and a speed of 800 r / min for 5 min, and sheared to obtain a mixed material;

[0043] S2. After 50% of the mixed material is evenly mixed with 2 parts of lithium bis(trifluoromethanesulfonic acid) amide, the remaining mixed material is added, and the material is mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes, and sheared to obtain a solid electrolyte material, which is recorded as PLA / PEG / EMA-g-GMA / 2L.

[0044] Example 4

[0045] A method for preparing a solid electrolyte material comprises the following steps:

[0046] S1, 60 parts of polylactic acid, 20 parts of polyethylene glycol (molecular weight 8000), and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer, mixed at a temperature of 200° C. and a speed of 800 r / min for 5 min, and sheared to obtain a mixed material;

[0047] S2. After 50% of the mixed material is evenly mixed with 4 parts of lithium bis(trifluoromethanesulfonic acid) amide, the remaining mixed material is added, and the material is mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes, and sheared to obtain a solid electrolyte material, which is recorded as PLA / PEG / EMA-g-GMA / 4L.

[0048] Comparative Example 1

[0049] The material of Comparative Example 1 is only polylactic acid, which is denoted as PLA.

[0050] Comparative Example 2

[0051] A method for preparing a solid material comprises the following steps:

[0052] 70 parts of polylactic acid, 20 parts of polyethylene glycol and 10 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer. The mixture was mixed at a temperature of 200°C and a rotation speed of 800 r / min for 5 minutes and sheared to obtain a mixed material, which was recorded as 70PLA / 20PEG / 10EMA-g-GMA.

[0053] Comparative Example 3

[0054] A method for preparing a solid material comprises the following steps:

[0055] 70 parts of polylactic acid, 10 parts of polyethylene glycol and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer. The mixture was mixed at a temperature of 200°C and a rotation speed of 800 r / min for 5 minutes and sheared to obtain a mixed material, which was recorded as 70PLA / 10PEG / 20EMA-g-GMA.

[0056] Comparative Example 4

[0057] A method for preparing a solid material comprises the following steps:

[0058] 60 parts of polylactic acid, 30 parts of polyethylene glycol and 10 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer. The mixture was mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes and sheared to obtain a mixed material, which was recorded as 60PLA / 30PEG / 10EMA-g-GMA.

[0059] Comparative Example 5

[0060] A method for preparing a solid material comprises the following steps:

[0061] 60 parts of polylactic acid, 20 parts of polyethylene glycol and 20 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer. The mixture was mixed at a temperature of 200° C. and a rotation speed of 800 r / min for 5 minutes and sheared to obtain a mixed material, which was recorded as 60PLA / 20PEG / 20EMA-g-GMA.

[0062] Comparative Example 6

[0063] A method for preparing a solid material comprises the following steps:

[0064] 60 parts of polylactic acid, 10 parts of polyethylene glycol and 30 parts of ethylene-methyl acrylate copolymer were mixed evenly and poured into a torque rheometer. The mixture was mixed at a temperature of 200°C and a rotation speed of 800 r / min for 5 minutes and sheared to obtain a mixed material, which was recorded as 60PLA / 10PEG / 30EMA-g-GMA.

[0065] The materials of Comparative Examples 1-6 were subjected to TG test according to GB / T 17050 standard. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen from the TG test results that with the introduction of blending components into PLA, the temperature at which the material begins to decompose will be reduced to a certain extent, but the overall temperature will still remain at a high level.

[0066] On this basis, a tensile test was further performed using an electronic universal testing machine to verify the mechanical strength of the blended material. The specific steps are as follows:

[0067] Weigh 22g of the above materials, put them into the mold, set the flat vulcanizer to pre-press for 2min, hot press for 5min, and then put the mold containing the masterbatch into the flat vulcanizer for hot pressing. When the hot pressing is over, the machine beeps, open the cooling water valve, put the mold into the lower layer for cold pressing for 2min, take out the sample after cold pressing, put it into a ziplock bag and label it. Place the pressed plate on the punching machine platform for punching, and make 5 samples for each group. The punched specimens are tested for mechanical properties using a microcomputer-controlled electronic universal testing machine, and the tensile strength, displacement, tensile strain at break and nominal strain at break are recorded in turn. The tensile strength and elongation at break are calculated based on the results. The results are shown in Table 1.

[0068] Table 1

[0069]

[0070]

[0071] It can be seen from the test results in Table 1 that as the content of polylactic acid decreases, the tensile strength decreases, but as the percentage of ethylene-methyl acrylate copolymer in the blended material increases, the tensile strength of the material also increases. The solid electrolyte material prepared by the embodiment of the present invention can effectively avoid the puncture of lithium dendrites in the actual application of solid-state batteries, thereby improving the safety performance of solid-state batteries; at the same time, different composition ratios of the embodiment can also be selected for different usage scenarios to meet different usage requirements.

[0072] The above materials were tested for ionic conductivity according to NB / T 10827-2021 standard. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen from the curve graph that the solid electrolyte material prepared by the present invention has a higher ionic conductivity.

[0073] Through the testing and characterization of the above materials, it can be seen that the overall performance of the invented material is excellent, with good mechanical properties, processing properties and electrical conductivity. The introduction of PEG increases PLA's ability to dissolve lithium salts. On the other hand, its own polar functional groups and the flexibility of the chain segments also greatly improve the ionic conductivity of the material. At the same time, adding ethylene-methyl acrylate copolymer to the material blend can also enhance the mechanical strength of the material. When used as a solid electrolyte, it can effectively prevent the puncture of lithium dendrites, thereby effectively improving the safety performance of solid-state batteries. By adding trace amounts of lithium salts to the blend, the ionic conductivity of the material can be further enhanced. The ionic conductivity of the test group PLA / PEG / EMA-g-GMA / 4L reached 10 -2S / cm, therefore, the invented material has a very broad application prospect as a solid electrolyte material. It can be based on PLA / PEG / EMA-g-GMA and add different conductive agents and other additives to meet the requirements of different solid-state batteries.

[0074] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a solid electrolyte material, characterized in that: The following steps are involved: S1. mixing and shearing the biodegradable material, polyethylene glycol and ethylene-methyl acrylate copolymer to obtain a mixed material; S2. After the first part of the mixed material and the lithium salt are evenly mixed, the second part of the mixed material is added, and the mixed materials are mixed and sheared to obtain a solid electrolyte material.

2. The preparation method according to claim 1, characterized in that: In the S1, the mass ratio of the biodegradable material, polyethylene glycol, and ethylene-methyl acrylate copolymer is (30-40):(5-15):(5-15).

3. The preparation method according to claim 1, characterized in that: In S1, the biodegradable material is selected from one or more of polylactic acid, polycaprolactone, polylactic acid-polyethylene glycol copolymer, and polydioxanone.

4. The preparation method according to claim 1, characterized in that: In the S1, the ethylene-methyl acrylate copolymer is ethylene-methyl acrylate grafted glycidyl methacrylate EMA-g-GMA, wherein the GMA monomer content is 5-12wt%, the methyl acrylate content is 22-26wt%, and the melt index is 3-8g / 10min.

5. The preparation method according to claim 1, characterized in that: In the step S1, the mixing conditions include: temperature 180-220° C., rotation speed 500-1000 r / min, and time 3-20 min.

6. The preparation method according to claim 1, characterized in that: In the S2, the lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl)amide, lithium phosphate and lithium sulfate.

7. The preparation method according to claim 1, characterized in that: In the S2, the mass ratio of the first part of the mixed material, the lithium salt, and the second part of the mixed material is (40-60):(0.5-5):(40-60).

8. The preparation method according to claim 1, characterized in that: In S2, the sum of the amount of the first part of the mixed material and the amount of the second part of the mixed material is equal to the total amount of the mixed material.

9. A solid electrolyte material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Biodegradable blend-type polymer electrolyte membrane and preparation method thereof

    CN102324483A

  • A biodegradable composite solid electrolyte membrane and a preparation method thereof

    CN109037766A

  • All-solid-state polymer electrolyte, preparation method and lithium ion battery

    CN110994014A

  • Composite electrolyte diaphragm, preparation method thereof and battery

    CN111916631A

  • Solid electrolyte membrane, preparation method thereof and battery

    CN118213606A